2000
DOI: 10.2307/2656860
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin banding patterns in Rutaceae‐Aurantioideae—a case of parallel chromosomal evolution

Abstract: The heterochromatin banding patterns in the karyotypes of 17 species belonging to 15 genera of Rutaceae subfamily Aurantioideae (= Citroideae) were analyzed with the fluorochromes chromomycin (CMA) and 4'-6-diamidino-2-phenylindole-2HCl (DAPI). All species were diploids, except one tetraploid (Clausena excavata) and two hexaploids [Glycosmis parviflora agg. (aggregate) and G. pentaphylla agg.]. There are only CMA/DAPI bands, including those associated with the nucleolus. Using recent cpDNA (chloroplast DNA) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
2
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 31 publications
9
73
2
5
Order By: Relevance
“…polyandra, M. australis, M. inodora, M. warburgiana, and Sydney hybrid were reported for the first time in this study; those of E. glauca and M. australasica have been previously reported (Guerra et al, 2000). Although the high reproducibility of CMA chromosome configuration is well known (Yamamoto, 2007), CMA banding patterns of these two species in the present study were not identical but were similar to those in studies by Guerra et al (2000). There is variability within species at least in M. australasica (Swingle and Reece, 1967).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…polyandra, M. australis, M. inodora, M. warburgiana, and Sydney hybrid were reported for the first time in this study; those of E. glauca and M. australasica have been previously reported (Guerra et al, 2000). Although the high reproducibility of CMA chromosome configuration is well known (Yamamoto, 2007), CMA banding patterns of these two species in the present study were not identical but were similar to those in studies by Guerra et al (2000). There is variability within species at least in M. australasica (Swingle and Reece, 1967).…”
Section: Resultsmentioning
confidence: 76%
“…These studies demonstrated the existence of characteristic CMA banding patterns with a high level of diversity and heterozygosity in the chromosomes of the above genera. The results also demonstrated CMA banding patterns of important species, which provide useful information on phylogenic relationships among these genera and species; however, CMA banding analysis of the other three genera has not progressed, although Guerra et al (2000) demonstrated CMA banding patterns of one species each of Eremocitrus and Microcitrus.…”
Section: Introductionmentioning
confidence: 96%
“…(Balsamocitrinae subtribe), a distant Citrus relative, in order to better distinguish donor pieces in the receptor genome background, which would be rather difficult if closer relatives were used due to greater similarities in their genomes. Swinglea glutinosa also presents a very distinct, heterochromatin-poor karyotype, and the smallest chromosomes known in the Aurantioideae subfamily (Guerra et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The fluorochrome DAPI preferentially stains AT-rich DNA, while CMA 3 preferentially stains GC-rich DNA. Guerra et al (2000), in studying the pattern of heterochromatic bands in Rutaceae, subfamily Aurantioideae, observed that the genus most basal in the group showed smaller amounts of heterochro-matin than did the more derived genera. Beyond fluorochrome banding, specific staining with silver nitrate or AgNOR can be used (Goodpasture and Bloom, 1975) to identify the nucleolus and chromosomes that have nucleolus organizer regions (NOR) that had been active in interphase.…”
Section: Introductionmentioning
confidence: 99%